The Proportionality Analysis in the Georgian Constitutional Jurisprudence and the Prospects of Rationality Review (Economic and Political Thought, 2019)
The proposed regulatory reform in Georgia introduces impact assessmenttool as part of the legislative process. While the lawmaker is accountableto the public and has a general duty to justify their actions, the politicalnature of parliamentary procedures makes it difficult to formally scrutiniselegislature. This paper looks into the argumentative strategy of constitutionaladjudication to showcase that the Georgian Constitutional Court possessesappropriate analytical framework to move towards realisation of rationalityreview of legislation.
Keywords: judicial review, rationality, proportionality, legal reasoning, impact assessment